Cost-Effectiveness Analysis of Psoriasis Treatment Modalities in Malaysia - Nor Azmaniza Azizam; Aniza Ismail; Saperi Sulong; Norazirah Md Nor (Kerman University of Medical Sciences, 2019)
Background There is limited evidence detailing the cost-effectiveness of psoriasis treatments in the Asian region. Therefore, this study is aimed to evaluate the cost-effectiveness of 3 psoriasis treatments tailored for moderate to severe psoriasis, namely topical and phototherapy (TP), topical and systemic (TS), and topical and biologic (TB) regimens, respectively. Methods This has been achieved by the participation of a prospective cohort involving a total of 90 moderate to severe psoriasis patients, which has been conducted at 5 public hospitals in Malaysia. The main outcome measures have been evaluated via cost and effectiveness psoriasis area severity index (PASI)-75 and/or body surface area (BSA)